Students’ Experience in Using Natural Reader Application to Ensure the Accuracy of Their English Pronunciation - Purnama, Yulian; Rintaningrum, Ratna; Nuswantara, Kartika; Trisyanti, Umi; Mark, Elladdadi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Since 1960, speech synthesis technology has existed and its applications are now widely available, one of which is the Natural Reader application. Natural Reader is an application that can be used in knowing how to pronounce words in English. This study aims to describe students' experiences with using the Natural Reader application and examine the effect of utilizing the use of the Natural Reader application as a tool to test the accuracy of pronunciation of Mahmud Yunus Batusangkar State Islamic University students, by using the Natural Reader application students can more easily test their English accuracy. The method used by researchers is quantitative method, quantitative research can show data containing numbers that can be obtained by utilizing google form as a means of making a questionnaire. This research shows that the Natural Reader application has the potential to ensure the accuracy of pronunciation in English. So it can be concluded that the Natural Reader device can ensure the accuracy of student pronunciation in English.